(untitled) (ModaPalavra e-periódico, 2016)
The aim of this paper is presenting Mi Piacce Methodology, which can be applied by shoe wearers to measure the pleasures provided by shoe design for women with lower limb dysmetria. Qualitative methodology was applied with mix techniques, such as comparative analysis of secondary sources, semi-structured interviews with five health professionals, and a phenomenological methodology with nine wearers. After this, it was develop Mi Piacce Methodology, and it was applied in forty-two wearers’ shoes design; eight are presenting in this paper. It can be concluded that the inconsistency in the degree of pleasures provided by the same style of shoes underlines the importance of conducting a holistic analysis to detect the strong and weak points of each shoe design for the wearer.